Recurrent hydatiform mole: a rare case report - Patil, Shaifali Kundan; Narshetty, Jaishree G.; Singh, Gursimran Baldev; Kurkal, Nidhi Sudhakar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Molar pregnancy is characterized histologically by abnormalities of the chorionic villi that consist of trophoblastic proliferation and oedema of villous stroma. The incidence of hydatiform moles in India is 1 in 1000. The incidence of recurrence is 1 in 60 in a subsequent pregnancy and 1 in 65 in the third pregnancy after two molar pregnancies. The occurrence of hydatiform mole is related to a few risk factors such as smoking, increased paternal or maternal age, and previous history of abortions. Here we report a case of a 29 year old woman with history of four partial moles and two first trimester abortions and her management. The patient finally opted for adoption.